Impact of agroecology on soil fertility status and cassava yield in Nigeria: II: contributions of soil properties to cassava yield variations - Asadu, C.L.A.; Nweke, F.I. (1999)
Cassava yields obtained from farmers' fields in Nigeria during the Collaborative Study of Cassava in Africa (COSCA) survey gave an average root yield of 14.5 t/ha and an average harvest index of about 0.56. The average root yields from both the sub humid and non humid zones were the same but significantly higher than that obtained from the humid zone. The soil properties which showed significant correlation with cassava yield parameters were sand, silt, clay, exchangeable Mn and Na, available P and OM as well as Mg:K and Mn:P ratios and exchangeable sodium percentage (ESP). Seven properties that contributed most to root yield variations were OM, pH, sand, exchangeable Ca, Mg and Mn, as well as ESP. The total variation accounted for by the soil variables was only 10% out of which Mn accounted for the highest proportion of about 3%. The overall contributions to other yield parameters were also low ranging from about 5% in shoot yield variation through about 10% in harvest index to about 12% in stand density. The overall low contribution was attributed to other environmental factors which influence cassava performance thus indicating that factors other than soil properties such as farmers' practices and climatic elements are also important determinants of cassava yield. Furthermore it was also see that nutrient ratios also made important contributions to cassava yield variations